A case study of early childhood development facility infrastructure in Philippi, South Africa - Siphe Madyibi; Amiena Bayat (Perspectives in Education, 2021)
Adequate infrastructure plays a critical role in early childhood development (ECD) facilities providing high-quality early learning services. An ECD facility is a partial care facility that provides an early childhood programme that encompasses early learning and the development of children before they start formal schooling. Hence early learning in South Africa is primarily accommodated in privately owned facilities that range from registered to unregistered facilities. For this reason, the inadequate infrastructure that characterises conditions under which most ECD facilities operate in South Africa has been noted with concern in numerous studies. This paper assesses the state of the physical infrastructure of ECDfacilities in Philippi, an impoverished township in the City of Cape Town in the Western Cape. Owing to the regulatory function of the state in the ECD sector, through which compliance standards have to be met to secure subsidisation, the authors analyse the impact of ECD legislation on the state of ECD infrastructure in Philippi. The analysis shows statistical differences in the infrastructure of 10 registered and 10 unregistered facilities. The infrastructure differs partly due to the registration status and the location in which the facilities are situated. We therefore deduce that the current state’s avoidance of infrastructure investment in ECD facilities amounts to the denial of positive early learning outcomes to these children in Philippi.